Penetration into dentin of sodium hypochlorite associated with acid solutions - Kuga, Milton Carlos [UNESP]; Gouveia-Jorge, Erica [UNESP]; Tanomaru-Filho, Mario [UNESP]; Maria Guerreiro-Tanomaru, Juliane [UNESP]; Bonetti-Filho, Idomeo [UNESP]; Faria, Gisele [UNESP] (Mosby-elsevier, 2011)
Objective. The objective of this study was to evaluate the penetration of 2.5% NaOCl associated with 17.0% EDTA, 1.0% citric acid, and 1.0% peracetic acid into dentin tubules.Study design. The roots of 44 bovine incisors were cross-sectioned and 5-mm-long fragments were produced from their middle thirds. The specimens were instrumented with ProTaper hand files, stained in crystal violet, then sectioned mesiodistally. The buccal fragments were divided into 4 groups (n = 9) and subjected to 2 consecutive 10-minute immersion periods in one of the following acid solutions combined with 2.5% NaOCl: 17.0% EDTA (group 1), 1.0% citric acid (group 2), and 1.0% peracetic acid (group 3). Nine fragments were immersed in 2.5% NaOCl (group 4). The analysis of the penetration of NaOCl solutions into dentin was performed by measuring the depth of crystal violet stain that was bleached using a steromicroscope under x50 magnification. Statistical comparisons were carried out by Kruskal-Wallis and Dunn's tests at the 5% significance level.Results. Group 1 showed less penetration into dentin than group 4 (P < .05). No statistically significant differences were observed among groups 2, 3, and 4 (P > .05).Conclusions. Association of NaOCl with acid solutions did not increase its penetration depth into root dentin. (Oral Surg Oral Med Oral Pathol Oral Radiol Endod 2011;112:e155-e159)